PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Wendy Salim Saputra (Jurnal Akuntansi Bisnis, 2018)
The company’s value serves as a measure of the success of the company's management in the prospect of future operations so as to realize the trust for the shareholders of the company, because if the welfare of the shareholders has been able to be met, then surely the circumstances reflect the high corporate value too. Company’s value can be influenced by several factors, such as Corporate Social Responsibility and Profitability The purpose of this research is to analyze the factors that affect the company’s value in manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2015. The research method used in this research is hypothesis test that is to analyze the influence of corporate social responsibility toward company’s value and influence profitability to company’s value. The analytical method used in this research is to use multiple regression analysis with statistic package testing tool for statistical package for social science (SPSS 22) for window. The results of this study indicate that the significance level for corporate social responsibility variables is 0.012 is smaller than 0.05 so it can be concluded that corporate social responsibility variables affect the company’s value, for the profitability variable the level of significance shows the value 0.000 smaller than 0.05 so it can be concluded Profitability variables affect the company’s value. Keywords:Corporate Social Responsibility, Profitability, Company’s Value